2003
DOI: 10.1634/stemcells.21-3-281
|View full text |Cite
|
Sign up to set email alerts
|

Multilineage Differentiation of Rhesus Monkey Embryonic Stem Cells in Three‐Dimensional Culture Systems

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 56 publications
0
44
0
1
Order By: Relevance
“…In order to solve the problems, 3D model arises at this historic moment. In recent years, many experiments were conducted to study the maintenance and differentiation of stem cells by 3D such as Embryonic Stem Cells are much easier differentiated into epithelial cells in collagen 3D culture [69] . In 3D culture, prostate progenitor cells (NHPrE1) with characteristics of stem cells appeared to be as dendritic growth and prostate epithelial stromal cells (BHPrE1) were not, suggesting that the former contains a higher proportion of stem cells / progenitor cells [70] .…”
Section: A Three Dimension (3d) In Vitro Modelmentioning
confidence: 99%
“…In order to solve the problems, 3D model arises at this historic moment. In recent years, many experiments were conducted to study the maintenance and differentiation of stem cells by 3D such as Embryonic Stem Cells are much easier differentiated into epithelial cells in collagen 3D culture [69] . In 3D culture, prostate progenitor cells (NHPrE1) with characteristics of stem cells appeared to be as dendritic growth and prostate epithelial stromal cells (BHPrE1) were not, suggesting that the former contains a higher proportion of stem cells / progenitor cells [70] .…”
Section: A Three Dimension (3d) In Vitro Modelmentioning
confidence: 99%
“…[89]) or for grafting procedures [13]. So far, other epithelial tissues have been successfully modelled in 3-D ECM cultures (see, for example [34,95]), and heterologous 3-D organotypic cultures have been extensively used in order to study interactions between different cell types in normal and pathological conditions ( [45,67,68] and references therein), to simulate in vitro human malignant tumours [25,81], to investigate factors that regulate stem cell fate [17], and to learn about virus-host interactions [2]. Table 1 lists the principal 3-D cell culture systems currently employed in basic and applied research.…”
Section: Toward Tissue-like Cell Systemsmentioning
confidence: 99%
“…In vitro differentiation into numerous lineages, including neural (Zhang et al, 2001;Rathjen et al, 2002;Wichterle et al, 2002;Nakayama et al, 2003), hematopoietic (Kaufman et al, 2001), osteo/chondrogenic (Buttery et al, 2001;Hegert et al, 2002;Sottile et al, 2003;Sui et al, 2003), myogenic (Muller et al, 2000;Kehat et al, 2001;Mummery et al, 2003;Zandstra et al, 2003), and endothelial (Yamashita et al, 2000;Kaufman et al, 2004) has been reported. For organ and tissue engineering, the intersection between directeddifferentiation by chemical means, such as growth factors and cytokines (Schuldiner et al, 2000), and innovative 3-dimensional culture techniques within biodegradable scaffolds and matrices (Kim and Mooney, 1998;Richardson et al, 2001;Chen et al, 2003;Levenberg et al, 2003;Liu et al, 2003) is likely to be particularly fruitful.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%